PENGARUH PERBEDAAN BAHAN PENGIKAT KARBOMER, METHYL CELLULOSA DAN KOMBINASINYA TERHADAP SIFAT FISIK SEDIAAN EYELINER DARI ARANG BATOK KELAPA - Rizki Febriyanti; Akhmad Aniq Barlian (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Eyeliner is a cosmetic that is often used by women, where eyeliner is an example of decorative makeup cosmetics that function to beautify and confirm the shape of the eyes. To develop eyeliner products, the important ingredients used are carbon and binder. The purpose of this study is to find out that carbon from coconut shell charcoal can be used as cosmetic eyeliner products with different binding materials and to find out formulas with binders that provide physical properties. best on eyeliner preparations from coconut shell charcoal. This study uses a laboratory experimental method that is by mixing carbomer binder, MC and a combination of both, 96% ethanol, paraben metal, aquadest, and adding activated carbon in it. The properties of the dosage were tested, namely homogeneity test, pH test, topical test, irritation test on voluntary skin, and test of preference for eyeliner preparations. The results showed that coconut shell charcoal can be used in eyeliner preparations and the formula which has the most preferred physical properties test is formula III with a carbomer and MC combination binder with a concentration of 1% eachKeywords: eyeliner, carbomer, MC, combination, physical properties test